Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships

Diplopyrone, a New Phytotoxic Tetrahydropyranpyran-2-one Produced by Diplodia mutila, a Fungus Pathogen of Cork Oak - Evidente, Antonio; Maddau, Lucia; Spanu, Emanuela; Franceschini, Antonio; Lazzaroni, Silvia; Motta, Andrea (Journal of Natural Products, 2003)
A new phytotoxic monosubstituted tetrahydropyranpyran-2-one, named diplopyrone (1), was isolated from the liquid culture filtrates of Diplodia mutila, a plant pathogenic fungus causing a form of canker disease of cork oak (Quercus suber). Diplopyrone was characterized, using spectroscopic and chemical methods, as 6-[(1S)-1-hydroxyethyl]-2,4a,6,8a-tetrahydropyran[3,2-b]pyran-2-one. The absolute stereochemistry of the chiral secondary hydroxylated carbon (C-9), determined by application of Mosher's method, proved to be S. Diplopyrone assayed at a 0.01?0.1 mg/mL concentration range caused necrosis and wilting on cork oak cuttings. On a nonhost plant, tomato, diplopyrone caused brown discoloration or stewing on the stem.
The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 12608876
Keywords: Phytopathogenic fungi; Phytotoxins; relative and/or absolute configuration; structure–activity relationships